LACUNA LEGIS PEMBERIAN KOMPENSASI BAGI KORBAN TRAFFICKING IN PERSONS DI INDOENSIA: Lacuna Legis in Compensation for Victims of Trafficking in Persons in Indonesia - Rahmania, Nunung; Ahwan, Ahwan (Ganec Swara, 2025)
Regulations related to compensation for victims of trafficking in persons within the Indonesian legal framework still leave significant lacuna legis, or legal gaps. The purpose of this study is to identify and analyze lacuna legis in the provision of compensation for victims of trafficking in persons in Indonesia. This study uses normative legal research with a legislative and conceptual approach. The results of the study show that there are lacuna legis in the TPPO Law, PSK Law, PP 35/2020, and PERMA 1/2022, which do not categorize victims of trafficking in persons as recipients of compensation. but instead limit the scheme only to victims of gross human rights violations and criminal acts of terrorism, thereby creating inequality in protection with victims of other crimes and contradicting the principles of modern victimology and the state’s obligations under international law, which require the state to provide effective recovery for all victims of serious crimes, including victims of trafficking in persons. The recommendation in this study is that it is necessary to reconstruct the compensation arrangements for victims of trafficking in persons as an effort to fill the legislative gap so that protection for victims of trafficking in persons is more inclusive, responsive, and in line with international standards